IN VITRO ANTIBACTERIAL ACTIVITY OF ONION (ALLIUM CEPA) AGAINST CLINICAL ISOLATES OF VIBRIO CHOLERAE - Hannan, Abdul; Humayun, Tabish; Hussain, Muhammad Barkaat; Yasir, Muhammad; Sikandar, Sumayya (Journal of Ayub Medical College Abbottabad, 2010)
Background: Cholera is a major public health problem in developing countries of the world. Bacterial resistance, lack of surveillance data and proper microbiological facilities are major problems regarding diagnosis of cholera. The spread of microbial drug resistance is a global public health challenge that results in increased illness and death rate. Newer antimicrobials or agents are urgently required to overcome this problem. This work was therefore done to investigate the antimicrobial potential of onion against thirty-three clinical isolates of Vibrio cholerae. Methods: The extract was prepared by reflux extraction method. Antibacterial screening of clinical isolates of V. cholerae was done by agar well diffusion method. Agar dilution method was used to assess the Minimum Inhibitory Concentration (MIC). Results: All tested strains of V. cholerae were sensitive to onion (Allium cepa) extracts of two types (purple and yellow). Purple type of extract had MIC range of 19.2-21.6 mg/ml. The extract of yellow type onion had an MIC range of 66- 68.4 mg/ml. Conclusion: The results indicated that onion (Allium cepa) has an inhibitory effect on V. cholerae. Keeping in view the anti-bacterial activity of this compound can be exploited as a therapeutic agent in an animal model. This finding is a positive point for further investigation of this herb of traditional medicine. Keywords: Vibrio cholerae, resistance, Allium cepa, antibacterial activity, extract